Innovation in small ruminants’ dairy products in Lebanon: an alternative drying technique for kishk, a traditional fermented milk - Salameh C.; Tabet E.; Hosri C.; Desobry-Banon S.; Scher J. (Innovation for sustainability in sheep and goats, 2019)
The Lebanese dairy sector is a viable and competitive sector. However, local dietary habits and consumer expectations of dairy products are changing, with a strong demand for innovative products with better hygienic and nutritional qualities. Consequently, it is essential to valorize traditional dairy products and improve their hygienic and nutritional quality, in order to increase their competitiveness in the Lebanese market and preserve this culinary heritage. Kishk is a traditional Lebanese fermented product, prepared from yogurt and bulgur allowed to ferment together, shaped into balls and sun-dried. However, the sun drying of kishk requires a large amount of manual labor for homogenous drying, and includes a high risk of microbial and physical contamination exists.Therefore, our study proposes an innovative drying technique (hot air drying at 50 °C for 8 h), and evaluates its effects on the nutritional, physicochemical and sensory properties of Lebanese kishk. Results showed that the structure and rheological behavior of kishk powder were not altered,despite slight differences in chemical composition and particle size. Furthermore, kishk soup resulting from the optimized production seems thicker and consistent than traditional soup, without significant loss of the organoleptic properties of kishk.Our results are promising and show that hot air drying technique can be a great alternative to improve the safety of kishk powder while preserving its nutritional and sensory quality.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)